Case report: An EEG captured case of migralepsy/migraine aura-triggered seizures - Hareem, Anam; Pahlavanzadeh, Mahsa; Calvo, Nicholas E.; Monjazeb, Sanaz; Anyanwu, Chinekwu (Frontiers in Neurology, 2022)
Migraine and epilepsy are common chronic neurological disorders presenting with paroxysmal attacks of transient cerebral dysfunction, followed by subsequent return to baseline between episodes. The term “migralepsy” has been proposed to define migraine-triggered epileptic seizures classified by the ICHD-III as a complication of migraine with an aura. A 55-year-old man with a 30-year history of migraine without aura presented with a new onset left parietal pain accompanied by visual disturbances occurring up to 20 times per day. His visual distortions were associated with kaleidoscopic pattern, flashes of shadows, and a right superior quadrantanopia lasting 20 minutes. In addition, he described discrete 2-minute episodes of scintillating scotomas in his right visual field. Ictal EEG demonstrated a left occipital onset focal aware seizure which correlated with his clinical symptoms. The patient was started on Valproic Acid and has remained asymptomatic. The diagnostic criteria as set out by the ICHD-III for migralepsy and other syndromes with migrainous and ictal features remain a source of confusion for practitioners as there is much overlap in clinical manifestations of these entities. EEG should be obtained when there is clinical suspicion of ictal features present in patients presenting with headache.